The Effect of Online Consumer Review on the Intention of Buying Products on Social Commerce - Muslimah, Nurul; Mursid, Mansur Chadi (APTISI Transactions on Management (ATM), 2019)
E-commerce is one form of evolution business models that adopt Web 2.0 technology with the aim of increasing consumer participation and gaining economic value ( greater economic value ) .This study aims to conduct confirmatory research on the relationship between social trade construction, online consumer review, trust and intention to buy through a questionnaire survey done to e-commerce users, especially students at Pekalongam IAIN using the purposive sampling method . The results of the collected questionnaires are then analyzed quantitatively using partial least square (PLS) . From the analysis and quantitative testing that can be done It was concluded that online consumer review does not have a direct influence on the intention to buy, but construction of trade has a direct influence on the buyer's trust and it is known that trust has a direct influence on the intention to buy.